USING VIDEO PROJECTS IN PROMOTING STUDENTS’ ENGLISH PARTICIPATION IN CONVERSATION CLASS - Meylina Meylina (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Videos are engaging. They teach students to plan, organize, write, communicate, collaborate, and analyze. This paper reports on a case study of the role of video projects in improving students’ participation in conversation class. Students’ low motivation in conversation class is presumbly caused by their less ideas to maximize the technology they had to draw in and connect them in innovative ways. This research is aimed at examining whether video projects can better improve students’ participation in English conversation. The result showed the improvements in terms of numbers of exchanges the students could produce in a conversation, students’ turn-taking, and students’ back-channeling. It indicated that video projects is really a great way to encourage students’ participation in conversation. As this media further matures, students may need to be able to express themselves as effectively through moving imagery as with the written word.